Comparison of Health-Promoting Lifestyle in Elderly with Depression and Healthy Elderly in Isfahan City, Iran, in Year 2018 - Narges Motamedi; Farnaz Feizi (مجله دانشکده پزشکی اصفهان, 2019)
Background: Given the high prevalence of depression in the elderly, as well as the importance of health-related lifestyle in the prevention of aging, this study was designed to compare the health-promoting lifestyle in elderly with depression and healthy elderly.